Pengelolaan Administrasi Perpajakan pada Pajak Bumi dan Bangunan Perdesaan dan Perkotaan oleh Badan Pendapatan Daerah Kota Serang Tahun 2022-2023 - Juliana; Cadith, Juliannes (Epistemik Press, 2025)
This study focuses on analyzing the administration of local taxes related to urban and rural land and building tax (PBB P2) at the Regional Revenue Agency (Bapenda) of Serang City during the period of 2022–2023. The objective of this research is to examine the implementation of local tax administration for PBB P2 in Serang City. A descriptive qualitative method is employed, utilizing the local tax administration theory proposed by M. Ikhsan and Roy V. Salomo, which outlines five key administrative stages: identifying tax subjects and objects, determining the taxable value, collecting and receiving tax payments, recording tax revenues, and enforcing tax laws or regulations. The findings reveal that the administration of PBB P2 in Serang City remains suboptimal, resulting in revenue targets not being fully achieved. Key challenges include discrepancies in PBB P2 object data, inadequate facilities and infrastructure for mobile tax services, limited human resources for tax assessments and the absence of enforcement officers, insufficient public outreach regarding PBB P2 payments, and a lack of strict enforcement of tax sanctions.